2016
DOI: 10.14359/51688825
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-Resistant Squat Walls Reinforced with High-Strength Steel

Abstract: Results are reported from reversed cyclic tests of five large-scale squat wall specimens reinforced with steel bars having a specified yield strength of either 60 or 115 ksi (413 or 792 MPa). Two specimens were designed for a shear stress of 5√f c ′ psi (0.42√f c ′ MPa) and the other three 9√f c ′ psi (0.75√f c ′ MPa). Boundary element confining reinforcement complied with the requirements of Chapter 18 of ACI 318-14 in all but one specimen, which had 50% of the required transverse boundary element reinforceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…Concrete cylinder strength was 6.4, 6.7, 4.8, 4.2, 7.3 and 7.4 ksi (44, 46, 33, 29, 50, and 51 MPa) for specimen H60 [4], H60_V, S4 [2], S9 [2], M1 [3] and M2 [3] respectively. Steel coupon test results are listed in Table 3.…”
Section: Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concrete cylinder strength was 6.4, 6.7, 4.8, 4.2, 7.3 and 7.4 ksi (44, 46, 33, 29, 50, and 51 MPa) for specimen H60 [4], H60_V, S4 [2], S9 [2], M1 [3] and M2 [3] respectively. Steel coupon test results are listed in Table 3.…”
Section: Test Resultsmentioning
confidence: 99%
“…Based on test result from Cheng et al [4], specimen H60 exhibited extensive deterioration along the base of the wall at the final state, as can be seen in Fig. 3(a).…”
Section: Overall Responsementioning
confidence: 97%
See 2 more Smart Citations
“…In order to validate the accuracy of the proposed model, the experimental database of 78 RC walls failed in shear is established, which includes the tests of Jang‐Woon Baek et al, Jang‐Woon Baek et al, Chung‐Chan Hung et al, Hong‐Gun Park et al, Min‐Yuan Cheng et al, Lefas et al, and Yoshizaki as reported by Hirosawa, Cardenas et al, Pedro A. Hidalgo et al, and Dabbagh . The 12 RC walls of Lefas et al, failed in shear were under monotonic loading, and the other 66 RC walls were under cyclic loading, and most of the walls were rectangular shear walls.…”
Section: Database Of Reinforced Concrete Walls Failed In Shearmentioning
confidence: 99%